2010
DOI: 10.1002/bip.21543
|View full text |Cite
|
Sign up to set email alerts
|

CD measurements of β‐amyloid (1–40) and (1–42) in the condensed phase

Abstract: Circular dichroism (CD) spectroscopy of proteins/peptides in thin films can provide valuable information on the structures in the aggregated states; however, it is difficult to estimate the secondary structure content quantitatively due to artifact signals arising from macroscopic anisotropies which is unique to the solid phase. Using a Universal Chiroptical Spectrophotometer (UCS-1) together with the measurement and analytical procedures we have developed, we could obtain artifact-free CD spectra of cast and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 29 publications
8
36
0
Order By: Relevance
“…CD analysis has been widely used to monitor secondary structure changes of proteins [53], [54], [55], [56]. The CD spectrum of Aβ monomer did not exhibit any spectral feature of α-helix and β-sheet, but showed typical features of dominantly disordered structure (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…CD analysis has been widely used to monitor secondary structure changes of proteins [53], [54], [55], [56]. The CD spectrum of Aβ monomer did not exhibit any spectral feature of α-helix and β-sheet, but showed typical features of dominantly disordered structure (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies using atomic force microscopy and scanning tunneling microscopy showed that the structures of dimers, tetramers, and other low-molecular-weight (MW) A␤ oligomers were consistent with the model of the A␤ monomers as ␤-hairpins (Losic et al, 2006;Mastrangelo et al, 2006). The most recent and accurate circular dichroism (CD) measurements of A␤ 1-40/42 (Harada and Kuroda, 2011) showed that A␤ peptides themselves have a strong tendency to form ␤-sheet rich structures during the transition to condensed phases, even without the help of a special effect of hydrophobichydrophilic interface.…”
Section: Introductionmentioning
confidence: 95%
“…7,[9][10][11][12][13] Despite such difficulties, there is a number of situations that demand the use of solid state rather than solution CD. [25][26][27] Second, the observation of chirogenic phenomena occurring in the solid state, which would be lost upon dissolution: these include the formation of crystals by spontaneous resolution of optically labile species, [28][29][30][31] co-crystals between a chiral species and an achiral or optically labile one, [32][33][34][35][36][37] and chiral crystals of achiral species. [25][26][27] Second, the observation of chirogenic phenomena occurring in the solid state, which would be lost upon dissolution: these include the formation of crystals by spontaneous resolution of optically labile species, [28][29][30][31] co-crystals between a chiral species and an achiral or optically labile one, [32][33][34][35][36][37] and chiral crystals of achiral species.…”
Section: Introductionmentioning
confidence: 99%